Коренные различия в строении и развитии сумчатых и плацентарных млекопитающих - Шмидт, Г.А. (Вестник зоологии, 1975)
The paper deals with four main groups of distinctions between marsupials and placentals: 1) absence of tertiary egg membranes; 2) sharp differences in the structure of the female urogenital organs in the placentals and marsupials; 3) absence of placental hormones in the marsupials; 4) accute variability in ways of larval organs development in the marsupials. All the above-mentioned peculiarities of the placentals are connected with their adaptation to cold climate.